Determinación de la curva de solubilidad de oxígeno para una emulsión de PFOB (2017)
"In this study, two methods are proposed to determine the solubility of oxygen in perfluorooctyl bromide emulsion (PFOB) in order to characterize its utility as a blood substitute. The first one consists in a fluorescence method in which a fluorophore (anthracene) changes its emission as a response to the dissolved oxygen concentration in the PFC. In the second method, the oxygen in the dispersed phase of the emulsion is quantified using the difference between the total oxygen absorbed in the emulsion and the existing one in the aqueous phase. For this, it was proposed to quantify what exists in the aqueous phase using an oxidation reaction, followed by a titration for ascorbic acid content. To estimate the amount of gas in the emulsion, it was proposed to use the oxygen partition coefficient in the experimentally found emulsion-gas system." -- Tomado del Formato de Documento de Grado.